Corporate Rebranding: An Employee-Focused Nonprofit Case Study. Issue 4 (1st October 2016) - Chad, Paul
ABSTRACT: The purpose of this paper was to examine the process by which a nonprofit organization conducted corporate rebranding and to assess the relevance of the principles of corporate rebranding originally developed by Merrilees and Miller (2008) in relation to for-profit organizations. A community-owned nonprofit organization that recently introduced corporate rebranding was examined. Semistructured in-depth interviews with employees from all organizational levels explored the rebranding process and employee feelings toward the process. Findings revealed that, while ultimately successful, rebranding did not progress smoothly. Problems related to initial management attempts to utilize minimal external expertise and to low levels of employee involvement and buy in. Findings suggest that all six principles of corporate rebranding proposed by Merrilees and Miller (2008) should be used by management as a guide to increase efficiency of the rebranding process and extends these principles to a nonprofit context. The paper also pioneers examination of corporate rebranding from a change management perspective.